The productive interplay between student-student and teacher-student dialogic interactions and the affordances of student generated explanatory drawings to understand plate tectonics - McLure, F.; Won, Mihye; Treagust, David (2023)
Understanding mechanisms underpinning formation of convection currents is pivotal for developing explanations of plate tectonics when teaching Geoscience topics. While student generated diagrams explaining convection currents may be used to evaluate student conceptual understanding and alternative conceptions in this topic, students may need support to produce elaborated explanatory diagrams. This study investigates the affordances of dialogue with peers and knowledgeable others as students construct explanatory diagrams of convection current formation and plate movement. Grade 8 students (n = 37) participated in small group and whole class discussions to construct explanations of plate movements at divergent boundaries and then drew diagrams to elaborate their understanding of this phenomenon. Throughout the process students were encouraged to mentally engage with the drawing process through discussions with peers and teachers. The drawing process provided opportunities for teachers to identify alternative conceptions that were not evident in teacher-student dialogic interactions but were evident in diagrams and to encourage consideration of scientific explanations through use of probing questions about what students were representing. The drawing process also elicited discussions between peers about complex interactions occurring within the mantle, during which some students became aware of inconsistencies within their explanations which led to adoption of more scientifically accurate conceptions.